The Influence Of Profitability On The Stock Price Of Construction Companies Listed On The Indonesia Stock Exchange For The Period 2019-2023 - Ahmad Imam Meilana; Syamsuddin Syamsuddin; Masrullah Masrullah (Jurnal Ekuilnomi, 2025)
This study aims to analyze the impact of profitability, measured by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), on the stock prices of construction companies listed on the IDX for the period 2019–2023. Utilizing a quantitative approach with secondary data from 19 companies, the analysis was conducted through multiple linear regression using SPSS 26. The results indicate that ROA and ROE have a positive and significant effect on stock prices, while NPM does not show significance. This finding reinforces the signal theory that high profitability serves as a positive signal for investors. This study is expected to contribute to investment decision-making and corporate financial strategy planning